PENGARUH INFLUENCER POLITIK DI MEDIA SOSIAL TERHADAP PARTISIPASI POLITIK GENERASI Z: STUDI KUANTITATIF PADA MAHASISWA UNIVERSITAS JAMBI DALAM KONTEKS PILPRES 2024 - Astia Rida Nurjannah; Dimasrizal; Aditya Romadhon; Mariatul Qibtiyah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study examines the influence of political influencers on social media on the political participation of Generation Z students at Universitas Jambi in the context of the 2024 Presidential Election. A quantitative approach was employed using a survey method involving 400 respondents selected through proportionate stratified random sampling. Data were collected through an online questionnaire using a Likert scale and analyzed using multiple linear regression. The results indicate that influencer credibility, two-way communication intensity, and audience engagement have a significant effect on students’ political participation, both simultaneously and partially. Influencer credibility emerged as the most dominant factor in shaping cognitive, affective, and behavioral political engagement. These findings confirm that political influencers function as opinion leaders in digital political communication and contribute to strengthening youth political participation at the regional university level.